Evaluation of pea/rice and amylopectin/chromium as an alternative protein source to improve muscle protein synthesis in rats - Ozdemir, Oguzhan; Erten, Fusun; Er, Besir; Orhan, Cemal; Komorowski, James R.; Sylla, Sarah; Şahin, Kazım (Springer Heidelberg, 2023)
BackgroundA preclinical study reported that the combination of an amylopectin/chromium complex (ACr) of branched-chain amino acids (BCAA) significantly enhanced muscle protein synthesis (MPS). This study was conducted to determine the effects of the addition of ACr complex to a pea/rice (PR) protein on MPS, insulin, muslin levels, and the mTOR pathway in exercised rats.MethodsTwenty-four rats were divided into three groups: (i) exercise (Ex); (ii) Ex + PR 1:1 blend (0.465 g/kg BW); (iii) Ex + PR + ACr (0.155 g/kg BW). On the day of single-dose administration, after the animals were exercised at 26/m/min for 2 h, the supplement was given by oral gavage. The rats were injected with a bolus dose (250 mg/kg BW, 25 g/L) of deuterium-labeled phenylalanine to determine the protein fractional synthesis rate (FSR) one h after consuming the study product.ResultsThe combination of PR and ACr enhanced MPS by 42.55% compared to the Ex group, while Ex + PR alone increased MPS by 30.2% over the Ex group (p < 0.0001) in exercised rats. Ex + PR plus ACr significantly enhanced phosphorylation of mTOR and S6K1 (p < 0.0001), and 4E-BP1 (p < 0.001) compared to the Ex (p < 0.0001). PR to ACr also significantly increased insulin and musclin levels (p < 0.0001) in exercised rats. Additionally, compared to Ex + PR alone, Ex + PR + ACr enhanced mTOR (p < 0.0001) and S6K1 (p < 0.0001) levels.ConclusionThese data suggested that PR + ACr may provide an alternative to animal proteins for remodeling and repairing muscle by stimulating MPS and mTOR signaling pathways in post-exercised rats. More preclinical and clinical human studies on combining pea/rice and amylopectin/chromium complex are required.
Keywords: Musclin; Insulin sensitivity; Amylopectin; chromium; Essential amino acids; Pea; rice protein blend